POPULAÇÃO NEGRA DISCENTE INGRESSA NA UNICENTRO: DIFICULDADES DE RECONHECIMENTO E PERTENCIMENTO - OLIVEIRA, TAUANA APARECIDA DE (2019)
This research addresses the ethnic-racial issue within the Midwest State University, as well as discusses the need for the quota system within the institution. The path taken goes through the analysis of documentary data regarding student enrollment between 2011 and 2017, analysis of government data according to IBGE on Brazil, Paraná and Guarapuava and data from “INEP” about higher education, interviews with people from the black movement of Guarapuava to collect information, analysis of the minutes of the responsible Councils for decisions regarding university admission processes: Minute number 184 of the Teaching, Research and Extension Council (“CEPE”) and Minute number 85 of the University Council (“COU”), statistical analysis of the registration data of students enrolled at UNICENTRO in the time frame of 2011-2017 and interviews using semi-structured questionnaires (31) for black students that have joined UNICENTRO. The main objective of this research was to analyze the barriers in relation to learning that black students encounter regarding belonging and recognition in the academic environment. The interpretation of the phenomena found was performed through Da Silva's Learning Constellations (2016; 2018; 2019). The Constellations were idealized at UNICENTRO thinking of the existence spaces in which the black student can go through, experiencing situations of social actions that we call positive or refractory actions for their learning and memories in the academic environment in relation to racism. Racism is trapped in society and consequently present in the university. Finally, it is concluded that the learning and experiences of black students who can enter the university receive too many refractory actions and lagging positive actions for their stay in UNICENTRO. We consider that the implementation of racial quotas at UNICENTRO would be just an initial step in a long path towards recognition and ethnic belonging of black students at this university. Other actions, such as the strengthening of collectives, institutionalization of “NEAA”, epistemological valorization of knowledge and black intellectuals in the course contents, insertion of black people in the administrative and leadership sectors of the university, appreciation of black culture and history, among others, are essential to positivize the blackness in the university.